Influence of the type of autonomic tone on the volume of the mucous membrane of the small intestine of laying hens - A. Tybinka; H. Blishch; O. Shchebentovska (Regulatory Mechanisms in Biosystems, 2018)
The connection between the separate structural parts of the mucous membrane of the small intestine of laying hens and the typological features of the autonomic tone were investigated. The studies were conducted on adult chickens of the cross-breed "Isa-Brown", which were divided into two groups: sympathicotonic chickens and sympathico-normotonic chickens, by the methods of electrocardiography and variation-pulsometry research. In the small intestine of the poultry of each group, the linear dimensions were determined first, and then the volume of the entire mucous membrane and its separate parts (villi, crypt, muscular plate), as well as the volume of connective tissue fibers in the crypt region. Research has shown that the villi account for ¾ of the volume of the entire mucous membrane. The volume of villi in the entire small intestine is more important in sympathico-normotonic chickens. This same poultry group has an advantage in the indicators of the volume of the muscular plate, but only in the duodenum and jejunum. In indicators of crypt volume, it turned out to be quite the opposite of the relationship with the typology of autonomous influences. In all studied intestines, the higher values of this indicator belong to the sympathotonic chickens. However, in terms of the volume of the entire mucous membrane, larger values still correspond to sympathico-normotonic chickens. Sympathicotonic chickens are inferior to them in the duodenum – at 1,005 mm3, in the jejunum – at 2,699 mm3 and in the ileum – only 78 mm3. Investigating the structure of the villi, we established that the volume of their epithelium in all three sections of the small intestine has higher values in the sympathico-normotonic chickens, and the larger volume of the lamina propria of the villi in the sympathicotonic chickens. At the same time, the connection with the type of autonomic tone is reflected in the ratio between the two layers of villi. In all three sections of the small intestine of sympathicotonic chickens, the ratio between the epithelium and the lamina propria was, on average, 65%/35%, or 2/1. In sympathico-normotonic chickens, this ratio varied and, on average, equalled 75%/25%, or 3/1. The increase in the tone of sympathetic centers contributes to the growth of volume both as the total amount of fibers of connective tissue, and also as separate elastic fibers in the area of crypt. According to the data,indicators of the sympathico-normotonic chickens are inferior to those of sympathicotonic chickens in all of the small intestine. It was also found that in both groups of poultry the volume of elastic fibers was approximately half the volume of all fibers of the connective tissue of the duodenum. In other sections of the small intestine, this figure was reduced to about ⅓. Consequently, the typological features of the autonomic tone, providing various trophic-regulatory effects on the mucous membrane of the small intestine, cause the formation of differences in its volume.